Financial Sustainability Of Microfinance Institutions In Kuningan Regency - Amir Hamzah; Febriansyah, Yudi (SKeTsa Bisnis (e-jurnal), 2025)
Introduction: This study investigates the influence of Financial Reporting Quality, Internal Control Effectiveness, and Financial Risk Behavior on the Financial Sustainability of Microfinance Institutions (MFIs) in Kuningan Regency from an accounting perspective. Method; Using a quantitative approach, data were collected from 116 respondents—including directors, managers, and finance heads of MFIs—through structured questionnaires and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). Results; The results show that Financial Reporting Quality and Internal Control Effectiveness positively and significantly affect financial sustainability, while Financial Risk Behavior has a significant negative impact, with the model demonstrating strong predictive power (R² = 0.984), thus emphasizing the role of accounting quality and rational decision-making in sustaining MFIs. Conclusion; These findings support the theoretical frameworks of Agency Theory and Behavioral Accounting Theory and suggest the importance of extending research beyond Kuningan Regency to include other influencing variables such as regulatory support or technological advancement.